Effectiveness of Educational Video Media to Increased Knowledge and Attitude in Knowing the Dangers of HIV/AIDS Disease In Adolescent Students Junior High School 2 Kupang City In 2020 - Yessicha Helmina Delly Tanof; Imelda F. E. Manurung; Sigit Purnawan (Journal of Health and Behavioral Science, 2021)
Abstract. Teenagers are the most vulnerable group physically and psychologically to HIV / AIDS infection, so teenagers become the focus of all strategies to combat the spread of HIV / AIDS virus, many educational media that can be used to provide information about the dangers and prevention of HIV / AIDS, one of which is video media. This study aims to find out the effectiveness of educational video media on the knowledge and attitude of students in knowing HIV / AIDS. This research was conducted with 3 research processes namely the Preparation stage, research data retrieval stage, and final research stage and this research using univariate and bivariate analysis where univariate analysis to find out the distribution and frequency of dependent variables (increased knowledge and attitude) and independent (educational video media) while the bivariate test used is paired t-test (Paired-sample t-test). The results of this study showed that educational video media is effective in increasing the knowledge and attitude of students in knowing the dangers of HIV / AIDS with a significance value of ρ = 0.00 or less (<) value of α 0.05. Video media can be used as one of the media informing about the dangers of HIV / AIDS in adolescent junior high school students.